Pengembangan Sistem Informasi Reservasi Pada CV. Dwi Artha Indah Samarinda Menggunakan Metode Rational Unified Process - Andhika Akbar Saputra; Yusi Tyroni Mursityo; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Dwi Artha Indah a company that provides event equipper service. However, the operational process in the company is still handled manually, hence problems arises, one of which is that the duration within checking the availability of equipment stocks often exceeds the procedure limit. Based on these problems, information system development is implemented to help the optimization of the company's business process. The development process is performed by using Rational Unified Process (RUP) development method, which was chosen due to its dynamic and iterative, so that it can respond to changes in needs that are not well defined. In the Inception phase, business process analysis will focus on leasing transactions, scheduling equipment delivery/pick-up, and reporting equipment repairs. Moreover, the elaboration phase, the results of the analysis of user requirements were found that the user needs include, 22 functional requirements and 1 non-functional requirement. Afterwards, the construction phase is carried out, the black-box testing was done through 39 test cases with the conclusion that the system can be run on 4 different browsers without fatal errors. The last phase is transition, the examination for the user acceptance test (UAT) was done in each actor with the results depict that the acceptance level on the admin actor reached to 88.88%, warehouse coordinator 88%, and the leader is 90%. Thus, it can be concluded that all actors are strongly agree with the system functionality. Through these development, its produced a information system that can support the management of leasing transactions, scheduling equipment delivery / pick-up, and reporting equipment repairs.